A familiar face: Student-teacher rematches and student achievement. (December 2021) - Hwang, NaYoung; Kisida, Brian; Koedel, Cory
Abstract: We use administrative data from Indiana to test whether student-teacher rematches in consecutive years affect student achievement. Using models that control for student and teacher fixed effects, we show that student-teacher rematches increase test scores in math and English Language Arts. The positive effects of rematching are constant over elementary and middle-school grades and more pronounced for historically underserved students. Our findings directly support strategies that aim to keep students and teachers together for longer periods of time during K-12 education. They are also consistent with the broader hypothesis that students benefit from increased student-teacher familiarity.